Engineering metaphase spindles: Construction site and building blocks. (December 2022) - Kletter, Tobias; Biswas, Abin; Reber, Simone
Abstract: In an active, crowded cytoplasm, eukaryotic cells construct metaphase spindles from conserved building blocks to segregate chromosomes. Yet, spindles execute their function in a stunning variety of cell shapes and sizes across orders of magnitude. Thus, the current challenge is to understand how unique mesoscale spindle characteristics emerge from the interaction of molecular collectives. Key components of these collectives are tubulin dimers, which polymerise into microtubules. Despite all conservation, tubulin is a genetically and biochemically complex protein family, and we only begin to uncover how tubulin diversity affects microtubule dynamics and thus spindle assembly. Moreover, it is increasingly appreciated that spindles are dynamically intertwined with the cytoplasm that itself exhibits cell-type specific emergent properties with yet mostly unexplored consequences for spindle construction. Therefore, on our way toward a quantitative picture of spindle function, we need to understand molecular behaviour of the building blocks and connect it to the entire cellular context.